Best practices of love pedagogy of educational leadership towards student academic excellence in cluster secondary schools Malaysia - Salleh, Mohamad Johdi; Hashim, Che Noraini (Fakulti Psikologi dan Pendidikan, Universiti Malaysia Sabah - UMS Kota Kinabalu Sabah, 2017)
Abdullah, Y.A., (2001). The Holy Quran, United Kingdom, Wordworth Editions Ltd. Ahamad, Z., & Kasim, A. L. (2016).Organizational Climate as a editor of the relationship between Transformational Leadership and Innovative Behavior in school.International Journal of Scientific Research and Education,4(04).p5168-5176. Allen, N., Grigsby, B., & Peters, M. L. (2015). Does Leadership Matter? Examining the relationship between Transformational Leadership, School Climate, and, Student achievement. International Journal of Educational Leadership Preparation,10(2), 1-22. Bear, G. G., Yang, C., & Pasipanodya, E. (2015). Assessing School Climate Validation of a Brief Measure of the Perceptions of Parents. Journal of psych educational assessment, 33(2), 115-129. Ginsberg, M.B., & Murphy, D. (2002). How walkthroughs open doors. Educational Leadership 59(8), 34-36. Hallinger, P. and Murphy, J. (1985).Assessing the instructional management behavior of principals.Elementary School Journal, 86 (2): 217-247. Harris, S.L., & Lowery, S. (2002). A view from the classroom. Educational Leadership 59(8), 64-66. Hatta, Muhammad. (2011). The Roles of Principal in Instructional leadership and School Performance. Kuala Lumpur: IIUM Press. Johnson, S.M., & Kardos, S.M. (2002). Keeping new teachers in mind. Educational Leadership 59(6), 12-17. Latip Muhammad. (2006). Implementation of Instructional Leadership among Principals of Selangor. PhD Thesis. Un-Published. Bangi: National University of Malaysia. Leithwood, k., Jantzi, D. and Steinbach, R. (1999) Changing Leadership for Changing Times, Buckingham: Open University Press. Mc Carley, T. A., Peters, M. L., & Decman, J. M. (2016). Transformational leadership related to school climate a multi-level analysis. Educational Management Administration & Leadership, 44(2), 322-342. Noddings, N. (1992). The challenge to care in school. New York: Teachers College Press. O’Malley, M., Voight, A., Renshaw, T. L., & Eklund, K. (2015). School climate, family structure, and academic achievement: A study of moderation effects. School Psychology Quarterly, 30(1), 142. Okorji, P. N., Igbokwe, I. C., & Ezeugbor, C. O. (2016). Relationship between school climate and principals' job performance in secondary schools. European Scientific Journal, 12(4). P55. Powel, W., & Napoliello, S. (2005). Using observations to improve instruction. Educational Leadership 62(5), 52-55. Safer, N., & Fleischman, S. (2005). How student progress monitoring improves instruction. Educational Leadership 62(5), 81-83. Southworth, G. (2002). Instructional leadership in schools: Reflections and empirical evidence. School Leadership & Management, 22(1), 73–92. Tajasom, A., Zainal, A., A. (2011) Principals ' leadership style and school climate: teachers' perspectives from principals’ leadership style and school climate : teachers ’ perspectives from Malaysia. The International Journal of Leadership in Public Services. 7 (4), 314-333.